The birth of modern Europe - Cairns, Trevor (London : Cambridge University Press, 1975)
Traces the history of Europe from 1500 to 1715, focusing on the role s played by religion and politics.
Keywords: Renaissance -- Juvenile literature; Reformation -- Juvenile literature; Europe -- History -- 1517-1648 -- Juvenile literature; Europe -- History -- 1648-1715 -- Juvenile literature; Europe -- History -- 1517-1648.; Europe -- History -- 1648-1715.